Long-term effects of chemotherapy in children with cancer - Lenny Gannika; Mulyadi Mulyadi; Gresty Natalia Maria Masi (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: Cancer is a non-communicable disease that poses a health problem worldwide, including in Indonesia, affecting not only adults but also children. The most commonly used cancer therapy is chemotherapy, yet it still has effects that can impact children both physically and psychologicallyPurpose: To identify the frequently experienced impacts of chemotherapy on children based on assessments conducted by parents at the